Pelatihan Manajemen Keuangan dan Pemasaran Digital untuk Mengembangkan Usaha Mikro - Eny Lintang Suryani; Zaskia Firnanda Efendi; Alexandra Shafa Ramadhani; Afifah Lutfiana Khoirunnisa; Muhamad Aditya Yulianto (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro-entrepreneurs, particularly small grocery shop owners, commonly encounter challenges in managing business finances and implementing effective marketing strategies. Limited skills in financial recordkeeping often make it difficult for business owners to accurately monitor cash flow and assess their financial condition, which may lead to suboptimal business decisions. In addition, the utilization of digital technology as a marketing tool remains limited, thereby restricting opportunities for market expansion. This community service program aims to strengthen the capacity of micro-enterprises in applying practical basic financial management and optimizing digital platforms for product promotion. The program also seeks to increase awareness of the importance of structured financial management as a foundation for sustainable business development. The activities were conducted through several stages, including the delivery of material on the significance of financial recording, hands-on training sessions, mentoring in preparing simple financial records, and digital marketing simulations using WhatsApp Business and various social media platforms. The results indicate an improvement in participants’ understanding and skills in recording income and expenses, managing business capital more systematically, and utilizing digital features to support promotional activities. Furthermore, participants demonstrated a more positive attitude toward the adoption of technology in their daily business operations. Overall, this program is expected to enhance financial independence, support sustainable business growth, and expand the marketing reach of micro-enterprises